Role of stress-related hormones in plant defence during early infection of the cyst nematode Heterodera schachtii in Arabidopsis - Kammerhofer, Nina; Radakovic, Zoran; Regis, Jully M A; Dobrev, Petre; Vankova, Radomira; Grundler, Florian M W; Siddique, Shahid; Hofmann, Julia; Wieczorek, Krzysztof (The New phytologist, 2015)
Heterodera schachtii, a plant-parasitic cyst nematode, invades host roots and induces a specific syncytial feeding structure, from which it withdraws all required nutrients, causing severe yield losses. The system H. schachtii-Arabidopsis is an excellent research model for investigating plant defence mechanisms. Such responses are suppressed in well-established syncytia, whereas they are induced during early parasitism. However, the mechanisms by which the defence responses are modulated and the role of phytohormones are largely unknown. The aim of this study was to elucidate the role of hormone-based defence responses at the onset of nematode infection. First, concentrations of main phytohormones were quantified and the expression of several hormone-related genes was analysed using quantitative real-time (qRT)-PCR or GeneChip. Further, the effects of individual hormones were evaluated via nematode attraction and infection assays using plants with altered endogenous hormone concentrations. Our results suggest a pivotal and positive role for ethylene during nematode attraction, whereas jasmonic acid triggers early defence responses against H. schachtii. Salicylic acid seems to be a negative regulator during later syncytium and female development. We conclude that nematodes are able to impose specific changes in hormone pools, thus modulating hormone-based defence and signal transduction in strict dependence on their parasitism stage.
Keywords: genetická transkripce; Chromatography, High Pressure Liquid; fyziologický stres; early infection; Cyclopentanes; biotest; Plant Diseases; Transcription, Genetic; Plant Growth Regulators; Heterodera schachtii; kyselina salicylová; Plant Immunity; Parasites; zvířata; regulace genové exprese u rostlin; cyklopentany; imunita rostlin; Gene Expression Regulation, Plant; Stress, Physiological; Arabidopsis; rostlinné geny; plant-parasitic nematodes; oxylipiny; regulátory růstu rostlin; Genes, Plant; kořeny rostlin; Oxylipins; Biological Assay; Tylenchoidea; nemoci rostlin; Salicylic Acid; salicylic acid; ethylene; Animals; jasmonic acid; defence responses; Plant Roots; hmotnostní spektrometrie; vysokoúčinná kapalinová chromatografie; paraziti; Mass Spectrometry